The construction client satisfaction model: a PLS-SEM approach - Durdyev, Serdar; Ihtiyar, Ali; Banaitis, Audrius; Thurnell, Derek (Journal of Civil Engineering and Management, 2018)
The satisfaction of the client is of utmost importance in procuring future projects; however, anecdotally client satisfaction (CS) is not adequately considered in many developing countries. Factors associated with the influence of service quality (SQ) on construction client satisfaction and how it affects their behavioural intentions in Cambodia are investigated. A theoretical structural model was developed to investigate the influence of five SQ factors on CS and their links to the future behavioural intentions of the client. A partial least square approach of the structural equation modelling technique (PLS-SEM) was employed to analyse data collected from a questionnaire survey of 227 participants comprising the clients of small and medium size projects. The structural model adapts 22 attributes across five SQ factors, namely: reliability; responsiveness; assurance; empathy, and tangible factors. PLS-SEM outcomes confirmed that the future behavioural intentions of the client are influenced by their satisfaction over the service excellence provided by construction companies. Moreover, treating every client individually and demonstrating an approachable attitude towards their needs will increase their satisfaction with the experience they had with a contractor. Findings and recommendations of the study may be useful to construction companies who are seeking ways to improve CS in developing countries.